High temperature corrosion behavior of alloys in reducing HCl and H2S containing environments: Thermodynamical and experimental assessment. Issue 12 (3rd August 2022) - Nimmervoll, Manuela; Mori, Gregor; Bucher, Edith; Hönig, Stefan; Haubner, Roland
Abstract: High‐temperature corrosion mechanisms in reducing atmospheres containing HCl (3.8 vol%) and a varying amount of H2 S (0.02 –2 vol%) were developed for several alloys between 420°C and 680°C. These mechanisms are mainly based on practical observations and kinetic considerations—and less on thermodynamic data. This is due to the complexity of these mixed gas atmospheres, volatile corrosion products, and the ever‐changing conditions within the corrosion layer, which made it not possible to predict and calculate the actual conditions in the corrosion zone. In this article, a detailed thermodynamic analysis of previously achieved corrosion mechanisms and experimental observations is presented. Correlations and deviations between thermodynamic calculations and practical findings are stated and discussed. The corrosion behavior of ferritic K90941, which performs worse than corrosion‐resistant austenitic alloys, except for one test condition at 580°C in the atmosphere with 0.2 vol% H2 S, is explained and supported by thermodynamic data. By combining experiments with thermodynamics, corrosion mechanisms in reducing HCl and H2S‐containing atmospheres are explained. Abstract : High‐temperature corrosion in reducing HCl and H2S‐containing atmospheres is challenging for commercially used alloys as several corrosive agents in the atmosphere show various different reactivities with the numerous alloying elements at different temperatures. Thus, the prediction of corrosion mechanisms in such environments is challenging. By means of thermodynamic data and experimental achieved findings, it is possible to assess such corrosion mechanisms.